Adalékok a Kárpát-medence kora középkori szőlőműveléséhez - Marton Szabolcs (University of Szeged, Magyar Medievisztikai Kutatócsoport Szeged, 2005)
The history of viniculture is a controversial matter in the research for the early Hungarian history and the lifestyle of early Hungarians. The author of this article adopts some new aspects for historical sources referring to early medieval viniculture, analysing e.g. the relevant parts of Capitulare de vil/is and Saint Gerard's Deliberado.
Keywords: Bölcsészettudományok; Történettudomány és régészet